Fertility Rates of Ewes Treated with Medroxyprogesterone and Injected with Equine Chorionic Gonadotropin plus Human Chorionic Gonadotropin in Anoestrous Season - I. W. Santos; L. C. Binsfeld; R. R. Weiss; L. E. Kozicki (Veterinary Medicine International)
The aim of the present paper was to investigate the efficiency of the equine chorionic gonadotropin (eCG) plus human chorionic gonadotropin (hCG) associated with medroxyprogesterone acetate (MAP) to estrous ewes synchronization. Ninety Texel ewes were investigated during seasonal anoestrous. The ewes received intravaginal sponges containing MAP (60 mg) for nine days. At the time of sponges' withdrawal, the ewes were divided into three groups (G): (1) receiving 2 mL of saline i.m. (n=30), (2) receiving eCG 400 IU i.m. (n=30), and (3) receiving eCG 400 IU plus hCG 200 IU i.m. (n=30). Twelve h after sponges' removal, teaser rams were used to estrus check and remained with the ewes for 96 h. The artificial insemination was made with fresh semen 10 h after estrus detection. The effect of the treatment was not significant for the estrous rates among the groups: 73%, 90%, and 86%, respectively. The main effect was observed in the pregnancy and lambing rates among the groups: 70%, 86%, 56%, and 80%, 120%, 56%, respectively. Based on these results from our study, the use of the MAP—eCG is the best choice to improve the fertility rate on ewes.